The Persona Analysis of the Clown Persona in Osamu Dazai’s A Shameful Life - Anwar Willy Andhika; Prayudias Margawati (Universitas Negeri Semarang, 2025)
Persona is one of Jung's archetypes, representing the mask or our other personality we make when we appear in front of people. The existence of personas is added to many forms of literature nowadays, especially in the character, which makes the story more complicated and enjoyable for the reader. Personas are given deep characteristics about the character's traits and psychological development. The novel